AKTIVITAS ANTIFUNGI EKSTRAK DAUN PEPAYA TERHADAP Candida Albicans PADA BASIS GIGI TIRUAN LEPASAN - Nugrahini, Sintha; Nurlitasari, Dewi Farida (Interdental: Jurnal Kedokteran Gigi, 2019)
Plaque accumulation on removable denture mayinduce Denture Stomatitis (DS). Candida albicans is the main microorganism that causes DS. To prevent DS, dentures need to be cleaned. The simplest denture cleaning method is immersion using chemicals. Papaya leaf (Carica papaya) contain antifungi substance, could be used as denture cleanser. The aim of this study wasto prove the effectivity of papaya leaf extract todecreasing the number of Candida albicans colonies on acrylic resin plates and thermoplastic nylon. This study was pretest-posttest with control group design, 32 samples (16 acrylic resin plates, 16 thermoplastic nylon plates) were divided into 4 groups: immersion using aquadest, fittydent®, papaya leaf extract 10% and 40%. Paired T-test showed the means of Candida albicans number on acrylic resin plates after immersion of aquadest, fittydent®, papaya leaf extract 10% and 40% were 0.75+2.98 CFU/ml, 82.5+1.29, 53.5+3.31 CFU/ml, 81.5+2.38 CFU/ml. The means of Candida albicans number on thermoplastic nylon after immersion of aquadest, fittydent®, papaya leaf extract 10% and 40% were 0.5+1.73 CFU/ml, 82.25+2.21 CFU/ml, 70.25+3.3 CFU/ml, 80.50+3.69 CFU/ml. Oneway ANOVA test showed no significant differences number of Candida albicans colonies (p >0.05) after immersion using fittydent® and papaya leaf extract 40% on both plates (100% Candida albicans cells died after immersion). The decrease percentage shown in the immersion of papaya leaf extract 10% group (66.67% on acrylic resin plates and 87.8% on thermoplastic nylon).This study concluded that papaya leaf extract was effective in decreasing the number of Candida albicans colonies on acrylic resin plates and thermoplastic nylon.